Normothermic Machine Perfusion as a Tool for Safe Transplantation of High-Risk Recipients - Manuel Durán; Angus Hann; Hanns Lembach; Anisa Nutu; George Clarke; Ishaan Patel; Dimitri Sneiders; Hermien Hartog; Darius F. Mirza; M. Thamara P. R. Perera (Transplantology, 2022)
Normothermic machine perfusion (NMP) should no longer be considered a novel liver graft preservation strategy, but rather viewed as the standard of care for certain graft–recipient scenarios. The ability of NMP to improve the safe utilisation of liver grafts has been demonstrated in several publications, from numerous centres. This is partly mediated by its ability to limit the cold ischaemic time while also extending the total preservation period, facilitating the difficult logistics of a challenging transplant operation. Viability assessment of both the hepatocytes and cholangiocytes with NMP is much debated, with numerous different parameters and thresholds associated with a reduction in the incidence of primary non-function and biliary strictures. Maximising the utilisation of liver grafts is important as many patients require transplantation on an urgent basis, the waiting list is long, and significant morbidity and mortality is experienced by patients awaiting transplants. If applied in an appropriate manner, NMP has the ability to expand the pool of grafts available for even the sickest and most challenging of recipients. In addition, this is the group of patients that consume significant healthcare resources and, therefore, justify the additional expense of NMP. This review describes, with case examples, how NMP can be utilised to salvage suboptimal grafts, and our approach of transplanting them into high-risk recipients.